Analysis of Politeness in Bilingual Indonesian–English Language Use in Elementary School Environments - Ricky Setiawan; Wahyu Sukartiningsih; Ulhaq Zuhdi; Bambang Edi Siswanto; Donne Jone Panizales Sodusta; Zeni Zakia Zamania (Studies in Learning and Teaching, 2026)
In elementary schools, the use of Indonesian and English not only serves as communication but also reflects the norms of politeness in social interactions. This study aims to describe the practice of politeness principles in Indonesian and English, as well as to analyze the level of politeness based on Brown and Levinson's scale in learning interactions in bilingual elementary schools, an area that has not been previously explored. This study uses a descriptive qualitative approach with data in the form of speech acts recorded during observations in the 5th grade of one of the elementary schools in Surabaya. Data were collected through listening, recording, and note-taking techniques. Data were analyzed using thematic analysis through the process of coding, categorization, and identification of language politeness patterns. Data validity was ensured through source triangulation, method triangulation, and member checking. The results showed that bilingual interactions were dominated by the directness and positive politeness strategies. Negative politeness and off-record strategies appear with limited frequency, especially when the level of stress is high or when teachers want to avoid direct criticism. These results suggest that politeness practices in bilingual classrooms are a balance between the need to foster a supportive learning atmosphere and hierarchical demands.